The Dynamics of Development of Islamic Civilization in the Reformation Period - Dimas A, Muhammad; Ayu Mustika Sari, Diyah (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2023)
The main objectives of this research are historical research on the dynamics of the development ofIslamic civilization during the Reformation Period is very interesting to study. It aims to describe thehistory of the Development of Islamic Civilization in the Reformation Period, and there are severalthings that include Socio-Cultural Conditions, Government Systems, Islamic Propagation Strategies,Challenges, and Influential Figures in the History of the Development of Islamic Civilization during theReformation Period.This study aims to analyze the dynamics of the development of Islamic civilizationduring the reformation period, the method we examine using the literature method produces datathat; 1.) Socio-cultural conditions during the reformation period can be said to be the worstdevelopments because during the reformation period many Indonesian people and immigrants wereethnocentric. 2.) The system of government during the reform period can be seen from the provinceof South Sulawesi, known as the Kingdom of Gowa, which was led by Sultan Hasanudin with hiscourage against Dutch colonialism. 3.) The strategy of Islamic da'wah has developed since enteringthe reform era, as evidenced by the number of Muslim population. 4.) Challenge. Viewed fromSulawesi, the dynamics of the spread of Islam cannot be said to face significant challenges, becausethe familial approach with autoplastic and alloplastic adjustments can change kings and communityleaders to become Muslims so as to form an Islamic empire. 5. Influential Figures Tahir Jalaluddin isan Indonesian scholar with expertise in astronomy and astronomy. He is a figure of the Islamic reformmovement in the Malay Peninsula. This study has implications for increasing literature on the historyof Indonesian Islamic civilization so that it can add to the scientific treasures of Nusantara Islam.